2011
DOI: 10.1111/j.1745-4557.2011.00390.x
|View full text |Cite
|
Sign up to set email alerts
|

Process Optimization for Chicken Patties Manufactured With a Combination of Spent Hen and Rabbit Meat

Abstract: A comminuted chicken patty was produced using spent hen and rabbit meats at 100:0, 95:5, 90:10, 85:15 and 80:20 ratios. The extenders/binders with whole liquid eggs (WLE) at 5, 10 and 15% and soy chunks at 3, 6 and 9%, respectively, were also used. The patties were evaluated for sensory, physicochemical and proximate quality and shelf life. The scores for all sensory attributes of patties stored at refrigerated temperature (4 ± 1C) for 20 days decreased significantly (P < 0.05) while pH, thiobarbituric acid an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
1
0
1
Order By: Relevance
“…Szentirmai et al (2013) stated the same when comparing TETRA SL brown, which were heavier than TETRA BLANCA white layers. Cooking loss from the sausages in the present study was quite high, but still not much higher than the 19% reported by Pawar et al (2011) for patties manufactured from spent hen meat. In contrast, Biswas et al (2006) only noted 10% cooking loss in patties from spent hens.…”
contrasting
confidence: 72%
“…Szentirmai et al (2013) stated the same when comparing TETRA SL brown, which were heavier than TETRA BLANCA white layers. Cooking loss from the sausages in the present study was quite high, but still not much higher than the 19% reported by Pawar et al (2011) for patties manufactured from spent hen meat. In contrast, Biswas et al (2006) only noted 10% cooking loss in patties from spent hens.…”
contrasting
confidence: 72%
“…Scores of all sensory parameters for two groups of sausages were in the range of 7.75 -8.31 (Good acceptability) which indicates acceptability of the chicken sausages. Similar trend is reported by Bhattacharyya et al, (2007) in spent duck sausages, Lengkey and Lobo (2016) in comparative study of chicken and rabbit low fat sausages, Pawar et al, (2011) in spent chicken patties and Sreenivasa Rao et al, (2011) in spent hen chicken sausages. Sausages made from spent broiler breeder hen meat had significantly superior scores in physico chemical and proximate analysis than sausages made from broiler meat and also noticed no significant difference in sensory scores between two groups of sausages.…”
Section: Sensory Evaluation Of Spent Broiler Breeder Hen and Broiler Chicken Sausagessupporting
confidence: 82%